Linkages between childhood emotional abuse and marital satisfaction: The mediating role of empathic accuracy for hostile emotions - Maneta, E.K. (Child Abuse Negl, 2014)
Research linking childhood emotional abuse (CEA) and adult marital satisfaction has focused on individuals without sufficient attention to couple processes. Less attention has also been paid to the effects of CEA on the ability to read other’s emotions, and how this may be related to satisfaction in intimate relationships. In this study, 156 couples reported on histories of CEA, marital satisfaction and empathic accuracy of their partners’ positive and hostile emotions during discussion of conflicts in their relationships. Actor-Partner Interdependence Modeling was used to examine links between CEA and marital satisfaction, with empathic accuracy as a potential mediator. Both men’s and women’s CEA histories were linked not only with their own lower marital satisfaction but also with their partners’ lower satisfaction. Empathic accuracy for hostile emotions mediated the link between women’s CEA and their satisfaction and their partners’ satisfaction in the relationship. Findings suggest that a history of CEA is associated with difficulties with empathic accuracy, and that empathic inaccuracy in part mediates the association between CEA and adult marital dissatisfaction.